Advanced energy and exergy analysis on aircraft jet engines - Fawal, Sara (Graduate School, 2023)
A comparative performance analysis for various optimization criterion functions is to be carried out for an irreversible Brayton cycle applicable to aircraft jet engines: Ramjet, Turbojet (No Afterburner), Turbojet (With Afterburner), Turbo-Ramjet. Newly defined parameters are introduced as power loss parameter (PLOS), effective power loss parameter (EPLOS) and Carnot-Brayton shape factor (CBSF) for a better assessment of the performance and power losses throughout the operation of the engine cycle. In addition, optimization functions, such as maximum power (MP), maximum power density (MPD), ecological coefficient of performance (ECOP) and ecological function (ECOL) are considered and their optimal operation conditions are compared with respect to each other. This research studied the effects on the prescribed optimization criterions targeted towards the aviation industry under variations of compressor pressure ratio θ_c, compressor and turbine efficiencies (η_c and η_t respectively), cycle temperature ratio / maximum cycle temperature, altitude and flight Mach number M_∞ where applicable with respect to the jet engine being considered. Therefore, the classical irreversible Brayton cycle is extended and applied to airbreathing engines; which included effects of all the engine components (from free stream to inlet to outlet) as part of the thermodynamic cycle model. While many researchers have carried out performance analysis for internal combustion engines including gas turbine engine, this study is an extension of the available optimization functions such as MP, MPD, ECOP and ECOL for aircraft jet engines. As mentioned, power density is defined as the ratio of power to the maximum specific volume in the cycle. Whereas ECOP is defined as the ratio of power output to the loss rate of availability and ECOL as the power output minus the loss rate of availability. In order to extend the classical irreversible Brayton cycle to airbreathing engines applicable for aircrafts, further development studies must be carried out to obtain: higher propulsion efficiency and higher ratios of power output with respect to engine weight, volume, and frontal area. The objective is to obtain a larger power output to engine size (weight) in a more thermodynamically efficient manner for a real turbojet cycle where maximum ECOP, ECOL, power density and power conditions can be used as a basis for the determination of optimal operating conditions and preliminary design constraints for real turbojet engines at flight conditions. The comparative performance analysis for various optimization criterion functions used for the aircraft engine cycle will be applied to ramjet, turbojet without afterburner and tubojet with afterburner to reach the final intended application of turboramjet engine. The turboramjet engine cycle is identified as Turbine Based Combined Cycle Engines (TBCC). Such hybrid cycle engines can be applied to UAV's, UCAV's and powering future hypersonic flight vehichles. The software to be used for the comparative performance analysis for the irreversible Brayton cycle applicable to aircraft jet engine cycles is the academic version of MATLAB 2018b provided by the MathWorks group. The emissions and radiative forcing (RF) from the aviation industry and its effects on air pollution and the ecology are an important concern, where aviation ranks as one of the top ten emitters. The major greenhouse gas emitters that contribute to RF are: carbon dioxide CO2, carbon monoxide CO, water H2O, nitrous oxide NOX, sulphur oxides SOX and volatile organic compounds VOCs. Thus, performance evaluation of aircraft propulsion systems must be assessed with respect to environmental and ecological conditions as well as power and fuel consumption considerations. Therefore, various optimization criterion functions which can be used as tools by the aviation industry to design 'new generation engines' which are economically and ecologically favourable. It is anticipated that this research would provide valuable insight in the preliminary design of airbreathing engines (Ramjet, Turbojet: No Afterburner, Turbojet: With Afterburner and Turbo-Ramjet) and set a stage for exploration towards adaptive engine components and cycles for the conception of truly intelligent engines; an engine that can assess its current operating state and work under the most efficient power regime (ECOL or ECOP or MP or MPD) to achieve the designers and engine's intended performance potential.
Havacılık jet motorlarında ileri enerji ve ekserji analizi
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: jet engines; jet motorları; exergy analysis; ekserji analizi